In silico based gene prediction and annotation of a local pathogenic ganoderma sp. Isolated from an oil palm plantation - Huda Mohamed Darul (2013)
Basal stem rot (BSR) which is caused by Ganoderma spp. is currently the most prevalent disease in Malaysian oil palm plantations which can causes infection of up to 80% of oil palms in an infected area within 15 years of plantation. As the main producer of palm oil and has the largest planted area of 1.43 million hectares in Malaysia, Sabah oil palm plantation is not excluded from the risk of infection by Ganoderma spp. Understanding the molecular mechanism underlying the pathogenesis of BSR is of primary importance to control the disease but there is limited number of genomic resources found at public databases. This present study aims to perform in silica based gene prediction and annotation of a local pathogenic Ganoderma sp. UMS isolated from infected palm oil tree at Langkon Oil Palm Estate in Sa bah. This involved the annotation of the possible genes and transcripts in Ganoderma sp. UMS set of contigs using two approaches, sequence similarity search and ab initio. Draft genome, EST, protein, RNA-seq data and gene model of the closely related species of Ganoderma lucidium which recently deposited to NCBI and JGI retrieved as the reference sequences. The 50.8-megabases assembled genome with an NSO of 6.24 kb and maximum contig length of 129.8kb predicted to encode about 15,624 genes by using AUGUSTUS and 12,250 of the predicted genes synthesized from evidence alignments using MAKER. Further assessment on the longest contig 140 showed total 38 genes was predicted with the average score of AED was 0.13. Blast2GO analysis provided functional annotation for 9226 genes. The knowledge gained from this Ganoderma sp. UMS draft genome will aid in the future functional genomic research to elucidate the host-pathogen interaction in BSR disease.